2015
DOI: 10.1093/rheumatology/kev392
|View full text |Cite
|
Sign up to set email alerts
|

Impact of tobacco smoking on response to tumour necrosis factor-alpha inhibitor treatment in patients with ankylosing spondylitis: results from the Danish nationwide DANBIO registry

Abstract: In this study of TNFi-treated AS patients in clinical practice, current and previous smokers had significantly poorer patient-reported outcomes at baseline, shorter treatment adherence and poorer treatment response compared with never smokers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 42 publications
3
57
1
1
Order By: Relevance
“…[25,26] An observational cohort study in 1576 Danish AS patient showed that current and previous smokers had worse treatment response to TNF-α inhibitors than never smokers. [27] Components of tobacco smoke can activate immune responses leading to higher secretion of pro-inflammatory cytokines. More inflammation and functional impairment may result in more new bone formation.…”
Section: Discussionmentioning
confidence: 99%
“…[25,26] An observational cohort study in 1576 Danish AS patient showed that current and previous smokers had worse treatment response to TNF-α inhibitors than never smokers. [27] Components of tobacco smoke can activate immune responses leading to higher secretion of pro-inflammatory cytokines. More inflammation and functional impairment may result in more new bone formation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, patients were recruited based on the diagnosis of expert treating rheumatologists and not on classification criteria. This could be considered an inherent limitation of most registries, wherein, comparable to our study, patients are included based on treating rheumatologists' diagnoses 10,15,27,28 . Nevertheless, we have to note that most of our patients had established, longstanding diseases; they were all followed by experienced rheumatologists, and baseline demographics and disease characteristics are well in accordance with available epidemiologic data and those reported by other registries 14,29,30 .…”
Section: Rheumatologymentioning
confidence: 99%
“…However, other response indices (ASDAS-ID, DAS28-inactive state, and ACR70) were not found to be associated with BMI (data not shown). Regarding smoking, conflicting available data exist in the literature, supporting either a negative effect or no role in drug survival 16,27 . In our cohort, both in univariate and multivariable regression analyses of available data (n = 234, 55% current, 12% past smokers, 33% never smoked), smoking status (treated either as ever/never or as non/past/current smoking) was not a significant predictor for TNFi survival overall (data not shown).…”
Section: Rheumatologymentioning
confidence: 99%
“…However, these registries more often address rheumatoid arthritis than axSpA. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] While retention rates for anti-TNFs have been investigated using several patient registries, their follow-up duration did not typically exceed 8 years. 4,5 Young age, male gender and presence of inflammatory syndrome appeared predictive of retention in most, ALthough not all cases.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Young age, male gender and presence of inflammatory syndrome appeared predictive of retention in most, ALthough not all cases. 4,7,11,12,19 Other debated factors include the anti-TNF type prescribed, presence of other arthritis forms, and using conventional synthetic disease-modifying antirheumatic drugs (csDMARDs) in combination with anti-TNF therapy. 10,11,14,16 In the event of treatment failure with a single anti-TNF, certain registries have assessed the efficacy of a second anti-TNF, ALthough with little data available on long-term retention.…”
Section: Introductionmentioning
confidence: 99%